THE FINANCIAL FEASIBILITY ANALYSIS FOR CONSTRUCTION PLAN OF FERRO-NICKEL (Fe-Ni) SMELTER PLANT AT SOUTH KONAWE REGENCY, SOUTH EAST SULAWESI - Harta Haryadi (Puslitbang tekMIRA, 2017)
The objective of the study is to comprehend the feasibility for construction plan of smelter plant to process the nickel laterite into ferro-nickel (Fe-Ni). PT. Macika Mineral Industries (PT. MMI), located at Lolowua village South Konawe, Southeast Sulawesi will implement such a plan Law No. 4 of 2009 on Mineral and Coal Mining obliges the mining investors to process the minerals into semi-finished or finished products in the domestic country before selling them abroad. The raw materials for PT. MMI smelter plant will be supplied by PT. Macika Mada Madana (PT. MMM) as one of PT. MMI group members PT. MMI is the holder of Production Operation Mining Permit that covers an area of 705 Ha and is located in Watudemba village, Palangga District and Keono Village, South Palangga District, South Konawe Regency. The mining area of PT. MMI is located 7 km from the PT. MMM planed plant. The total Ni reserve owned by PT. MMM is 18,930,700 tons. Of 18,930,700 ton reserves; 4,390,645 tons belongs to the measured one performing the average grade of nickel and iron around 1.97 and 23.14% respectively while around 14,540,055 tons that contain the average grade of nickel and iron about 1.92 and 23.14% respectively goes to the inferred reserve. PT. MMI requires 960,000 tons per year of Ni raw material it means that PT. MMM can supply the processing plant up to 20 years. Net present value (NPV), internal rate of return (IRR), return on investment (ROI), payback period (PBP), benefit cost ratio (B / CR), and breakeven point (BEP) are the criteria for evaluating the financial need of PT. MMI. The results showed that the NPV was about US 726,883,479 while the IRR and the ROI were around 18.00% and 212.90% respectively. Calculating the PBP and the B/C achieved 6.19 years and 3.21 correspondingly. The reached BEP was US 754 per ton for the production of 50,504 tons. The analysis showed that the construction of ferro-nickel (Fe-Ni) plant by PT. MMI was financially acceptable to be. However, using several variable measurements in analyzing the sensitivity of the business, namely by the selling price of ferro-nickel is assumed to be reduced by 5% and production cost is increased by 5%, the plan is not sensitive to decreasing selling price and increasing production cost.